FLL2 modulates Arabidopsis development and stress tolerance via polyadenylation and CPSF73 interaction - Saiqi Hao; Danhui Zhao; Congting Ye; Haidong Qu; Xiangming Zhou; Qingshun Q. Li (iScience)
Summary: The coiled-coil protein FLL2 is known to promote liquid–liquid phase separation in the polyadenylation complex, however, the role of FLL2 in polyadenylation remains unclear. Here, we investigated the impact of a developmental mutant sof78 in FLL2 gene of Arabidopsis leading to many effects on primary root, flowering time and developmental alterations, and tolerance to oxidative stress. To explore the relationship between FLL2 and CPSF73, we employed a boron-containing benzoxaborole compound AN3661, a known inhibitor of the poly(A) factor CPSF73. Our results indicate when treated with AN3661, the phenotypic responses of the sof78 mutant were similar to that control line C2, suggesting both CPSF73 and FLL2 co-modulated the growth and adaptation. Using poly(A) tag sequencing (PAT-seq) to compile poly(A) sites at the transcriptome level, we discovered 2.2%–12.8% of significant differentially expressed alternative polyadenylation (APA) events were changed in sof78, upon AN3661 or oxidative treatment. Under such conditions, transcripts in sof78 exhibited a preference of less U and more G in their poly(A) signals, along with decreased the usage of canonical poly(A) sites in 3′UTRs but increased the usage of non-canonical poly(A) sites in other genic regions. Gene ontology analyses demonstrate that these APA genes are enriched in abiotic stress, osmotic stress, auxin signaling, and ethylene signaling pathways, which were identified and linked to respective phenotypes. These results provide functional linkages between FLL2 and CPSF73 mediated by APA in critical genes for plant development and environmental responses.